2020
DOI: 10.1007/s00382-020-05552-4
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of thermodynamics and ocean dynamics during ENSO growth phase

Abstract: The growth of El Niño/Southern Oscillation (ENSO) events is determined by the balance between ocean dynamics and thermodynamics. Here we quantify the contribution of the thermodynamic feedbacks to the sea surface temperature (SST) change during ENSO growth phase by integrating the atmospheric heat fluxes over the temporarily and spatially varying mixed layer to derive an offline “slab ocean” SST. The SST change due to ocean dynamics is estimated as the residual with respect to the total SST change. In observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 59 publications
(117 reference statements)
1
25
0
Order By: Relevance
“…In (Bayr et al 2019(Bayr et al , 2021. In reanalysis data, 1 K of SST change during an ENSO event in the Niño3.4 region goes along with a forcing of + 2.3 K/K by the ocean dynamics and a Q net damping of -1.3 K/K, mainly by the SW feedback amounting to -0.8 K/K and the LH feedback amounting to -0.5 K/K (Fig.…”
Section: Relation Between Mean State Changes and Enaf Changesmentioning
confidence: 93%
See 3 more Smart Citations
“…In (Bayr et al 2019(Bayr et al , 2021. In reanalysis data, 1 K of SST change during an ENSO event in the Niño3.4 region goes along with a forcing of + 2.3 K/K by the ocean dynamics and a Q net damping of -1.3 K/K, mainly by the SW feedback amounting to -0.8 K/K and the LH feedback amounting to -0.5 K/K (Fig.…”
Section: Relation Between Mean State Changes and Enaf Changesmentioning
confidence: 93%
“…The contribution of the thermodynamics and ocean dynamics to the SST change during ENSO growth in the Niño3.4 region is estimated by a method proposed by Bayr et al (2019Bayr et al ( , 2021: The net heat ux Q net is integrated over the 6 months preceding the maximum of each ENSO event:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that water and energy flux anomalies during ENSO dominate the SPCZ shift. Other study by Bayr et al (2021) quantified the thermodynamic feedbacks between the ocean and the atmosphere through sea surface ENSO influence over Northern South America temperatures (SSTs) and heat fluxes simulated by climate models. They suggest that the better representation of thermodynamic feedbacks between the ocean and the atmosphere, the more realistic simulation of ENSO events.…”
Section: Introductionmentioning
confidence: 99%